Mutagenicity and Acute Oral Toxicity Test for Herbal Poultry Feed Supplements - Boddapati Srinivasa Rao; C. V. Chandrasekaran; H. S. Srikanth; Murugan Sasikumar; R. Edwin Jothie; Begum Haseena; Bethapudi Bharathi; Ramasamy Selvam; D’Souza Prashanth (Journal of Toxicology)
Herbal products are being used and trusted globally for thousands of years for their health benefits and limited side effects. Globally, a general belief amongst the consumers is that herbal supplements are always safe because they are “natural.” But later, research reveals that they may not be safe. This raises concern on their safety and implications for their use as feed supplement or medicine. Toxicity testing can reveal some of the risks that may be associated with use of herbs, therefore avoiding potential harmful effects. The present study was designed to investigate five poultry feed supplements (PFS), EGMAX® (to revitalize ovarian activity), FEED-X™ (feed efficiency enhancer), KOLIN PLUS™ (natural replacer of synthetic choline chloride), PHYTOCEE® (natural defence enhancer), and STODI® (to prevent and control loose droppings), for their possible mutagenicity and toxicity. Bacterial reverse mutation (BRMT) and acute oral toxicity tests were employed to assess the PFS for their possible mutagenicity and toxicity. Results indicated that the PFS were devoid of mutagenic effects in BRMT and showed higher safety profile in rodent acute oral toxicity test.